Áreas protegidas e assentamentos rurais em Sergipe: sob o enfoque do princípio constitucional do desenvolvimento sustentável - Costa, Sandro Luiz da (2016)
The interaction between rural settlements of agrarian reform under supervision of INCRA and environmental protected areas has been propagated in the media as negative from the point of view of the constitutional principle of sustainable development. The present work evaluates the process of interaction between the legal system of environmental protected areas and rural settlements of the State of Sergipe, correlating the parameter of legal effectiveness, under the focus of the constitutional principle of sustainable development. To achieve this goal stood up the theoretical, instrumental and legal apparatus that discipline the protected areas and rural settlements in Brazil; was accomplished the characterization of rural settlements in Sergipe in relation to protected areas; the relationship identified between protected areas and rural settlements in Sergipe and, finally, the obstacles and the potential of these settlements were analyzed in relation to the occupation of protected areas. For this, apart from documentary research, were made visits to Settlements projects specified in the sample. As a result, in addition to the presentation of the instruments and the legal system governing the relationship between protected areas and settlements in Brazil, were established the potentials and obstacles of that system and suggested sustainable alternatives when necessary.